A Tunable low Pass Filter Based on Transmission Lines With Tunable Input/Output Impedance - Zhang, Zhonghai; Zhao, Yuekai; Chen, Lin; Fang, Zhihua; Wu, Aiting; Zhang, Pengquan (Frontiers in Physics, 2022)
A tunable low pass filter(TLPF) based on the tuning of input/output impedance was presented in this letter. The TLPF was mainly consisted of improved quarter-wavelength stubs. The input/output impedance of the improved quarter-wavelength stubs can be tuned in certain range. The design procedure of this TLPF was derived from the filters based on the quarter-wavelength transmission stubs. Through the tuning of the input/output impedance of the transmission lines, the cut-off frequency of TLPF can be adjusted in certain range. The TLPF has relatively good designability and can be easily designed to meet other performance. Finally, a TLPF was designed, fabricated and measured. The measured results verify the effectiveness of the design method.